Biotoxic impact of heavy metals on growth, oxidative stress and morphological changes in root structure of wheat (Triticum aestivum L.) and stress alleviation by Pseudomonas aeruginosa strain CPSB1. (October 2017) - Rizvi, Asfa; Khan, Mohd. Saghir
Abstract: Rapid industrialization and uncontrolled metal discharge into environment is a global concern for crop production. Metal tolerant bacterium isolated from chilli rhizosphere was identified as Pseudomonas aeruginosa by 16S rDNA sequence analysis. Pseudomonas aeruginosa tolerated high concentrations of Cu (1400 μg ml −1 ), Cd (1000 μg ml −1 ) and Cr (1000 μg ml −1 ). Pseudomonas aeruginosa CPSB1 produced multiple plant growth promoting biomolecules in the presence and absence of metals. Strain CPSB1 solubilized P at 400 μg ml −1 of Cd, Cr and Cu. The strain was positive for indole-3-acetic acid (IAA), siderophores, hydrogen cyanide (HCN), ammonia (NH3 ) and 1-aminocyclopropane-1-carboxylate (ACC) deaminase when grown with/without metals. The phytotoxic effects on wheat increased with increasing Cd, Cr and Cu rates. The P. aeruginosa CPSB1 inoculated wheat in contrast had better growth and yields under Cu, Cd and Cr stress. The root dry biomass of inoculated plants was enhanced by 44, 28 and 48% at 2007 mg Cu kg −1, 36 mg Cd kg −1 and 204 mg Cr kg −1, respectively. The bioinoculant enhanced number of spikes, grain and straw yields by 25, 17 and 12%, respectively. Pseudomonas aeruginosa CPSB1 significantly declined the levels of catalase (CAT), glutathione reductase (GR) and superoxide dismutase SOD), proline and malondialdehyde (MDA), and reduced metal uptake by wheat. The study demonstrated that P. aeruginosa CPSB1 possessed plant growth promoting potentials, showed metal tolerance capability and had ability to counteract deleterious metal impacts. Due to these, P. aeruginosa CPSB1 could be used as bioinoculant for enhancing wheat production even in metal contaminated soils. Highlights: Phytotoxic impacts of metals on wheat varied from species to species. Metal tolerant Pseudomonas aeruginosa synthesize plant growth promoting biomolecules even in the presence of heavy metals. Heavy metals destruct wheat root morphology. Pseudomonas aeruginosa CPSB1 alleviates metal toxicity to wheat plants. P. aeruginosa reduced the level of proline and antioxidant enzymes.